Radical polymerization of dimethylacrylamide (DMAM): a computational study - Kura, Berkehan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Since free radicals are highly reactive species, free radical polymerization proceeds fast and high molecular weight polymers are synthesized in a short period of time. This fact makes free radical polymerzation favored in industry. However, controlling the tacticity of the synthesized polymer is not easy in free radical polymerization. Controlling tacticity of a polymer is important because tacticity designates many physical properties of a polymer. Isobe group found that Lewis acid, used as a catalyst favors the isotacticity of polyacrylamides, especially in methanol. Dimethylacrylamide (DMAM) is one of those acrylamides that they study. In this study, it is desired to model the propagation step of polymerization of DMAM. Dimeric and trimeric chains are modeled with and without ScCl3. Transition states and reactants are optimized and propagation rates are designated for isotactic and syndiotactic polymerization pathways. Our results supports the idea that multicoordination properties of Lewis acids favor the isotacticity.
Keywords: Polymers.; Addition polymerization